Left atrial function and mortality in the oldest old. Issue 12 (16th December 2017) - Leibowitz, David; Koslowsky, Jonathan; Gilon, Dan; Jacobs, Jeremy M.; Stessman‐Lande, Irit; Stessman, Jochanan
Abstract : Background: Previous studies demonstrated that left atrium (LA) size is associated with mortality in an elderly population. It remains unclear whether indices of LA function including reservoir, conduit, or booster elements of LA function provide incremental prognostic information. Hypothesis: Echocardiographic measures of the various parameters of LA function would predict 5‐year mortality in a community‐dwelling population of 85 to 86 year olds independently of LA volume. Methods: Subjects ages 85 to 86 years old underwent home echocardiography. LA volumes were assessed by the biplane Simpson's method from apical views using measurements of phasic volumes and functions of the LA, including LA expansion index. LA passive and active emptying fractions were assessed. Survival status at 5‐year follow‐up was assessed. Results: Two hundred eighty‐two subjects were included, of whom 87 (31%) had died at follow‐up. Survival of the subjects in the lowest quartile of the LA expansion index as well as LA active filling index was significantly lower. When measurements of LA volume index were added to the model, the relationship between survival and indices of LA function remained significant. Conclusions: This study demonstrated that elderly subjects aged 85 to 86 years with significantly impaired LA function had increased 5‐year mortality independently of indices of LA volume.